USING GOOGLE FORMS AS AN ONLINE GERMAN EXAM MEDIA FOR STUDENTS OF MALANG SENIOR HIGH SCHOOL - Mardini, Dita Kurniati (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
This study aimed to describe the use of Google Forms as a medium of an online exam in a German course, along with the results. This study was conducted using a qualitative descriptive method. The main instrument in this study was the researcher and supported by other instruments in the form of questionnaires and interview guidelines. The data sources in this study were collected from 26 students of class 12 IPS 1 who took a German Language cross-major course at SMAN 6 Malang. Based on the results of this study, it can be concluded that Google Forms was an effective application to use during an online exam. Based on the result of interviews, students highly recommended the Google Forms application to be used as an online exam medium because of its practicality and convenience. Students also did not experience any difficulties during the online exam process using Google Forms.